Mammalian miRNA curation through next-generation sequencing - Brown, Miguel; Hafner, Markus; Farazi, Thalia; Tuschl, Tom (Frontiers in Genetics, 2013)
Characteristic small RNA biogenesis processing patterns are used for the discovery of novel microRNAs (miRNAs) from next-generation sequencing data. Here, we highlight and discuss key criteria for mammalian – specifically human – miRNA database curation based on small RNA sequencing data. Sequence reads obtained from small RNA cDNA libraries are aligned to reference genomic regions, and miRNA genes are revealed by their distinct read length and bimodal read frequency distribution, the predicted secondary structure of the deduced miRNA stem-loop precursor molecule, and, to a lesser degree, based on evolutionary conservation of small RNAs from other vertebrates. Properly curated miRNA databases are an important resource for investigators interested in miRNA biology, diagnostics, and therapeutics.